Evaluation of Wound Healing Property of Karanja Patra Ghana Water Extract of Pongamia pinnata Linn Leaf - Sunil Kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Evaluation of Wound Healing Property of Karanja Patra Ghana Water Extract of Pongamia pinnata Linn Leaf